2020
DOI: 10.32371/jfp/246099
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Preservation Discussion in Adult Male Cancer Patients Is Underutilized and Varies Based on Age

Abstract: Introduction. Oncofertility is often omitted in pretreatment discussion and planning. This study seeks to evaluate the prevalence and influencing factors of cryopreservation discussions. Methods. A retrospective review was performed on 3,133 male patients aged 18-60 years with a cancer diagnosis at a single institution. Data was collected for cryopreservation discussion and if cryopreservation of sperm was performed. Age, race, cancer location, primary treatment, and chemotherapy status were also recorded. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Identifying barriers to FP is vital as cancer survivorship improves and FP techniques advance. Perhaps the most critical barrier is still that of low referral rates 2,5 ; however, the establishment of formal oncofertility programs nationwide has promisingly led to increased referrals. 15,16 A unique characteristic of our study is that it only includes men who were referred for FP, thereby eliminating the most prevalent confounding variable from our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying barriers to FP is vital as cancer survivorship improves and FP techniques advance. Perhaps the most critical barrier is still that of low referral rates 2,5 ; however, the establishment of formal oncofertility programs nationwide has promisingly led to increased referrals. 15,16 A unique characteristic of our study is that it only includes men who were referred for FP, thereby eliminating the most prevalent confounding variable from our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary studies have demonstrated that , 30% of eligible men are referred for FP and , 15% eventually cryopreserve sperm. 2,5,6 Numerous reasons for this underutilization have been proposed and generally fall into three categories: patient/family, provider, and institutional barriers. [7][8][9] For many patients, costs, severity of illness, and cultural or psychosocial factors may preclude timely cryopreservation.…”
Section: Effect Of Distance From Fertility Center On Utilization Of F...mentioning
confidence: 99%